New species of Rivudiva Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae) with comments on R. minantenna Lugo-Ortiz & McCafferty and R. trichobasis Lugo-Ortiz & McCafferty - Salles, F.f.; Nieto, C.; Cruz, P.v. (Zootaxa, 2020)
Based on nymphs collected in Espírito Santo and Amazonas, Southeastern and Northern Brazil, two new species of the genus Rivudiva Lugo-Ortiz & McCafferty, 1998 (Ephemeroptera: Baetidae) are described. Rivudiva inma sp. nov. shares several characteristics with R. minantenna Lugo-Ortiz & McCafferty, 1998, but can be distinguished by details of leg setation, such as length and shape of robust setae and presence of setae on trochanter. Rivudiva oonirikoperi sp. nov. is more similar to R. trichobasis Lugo-Ortiz & McCafferty, 1998, but can be separated by the absence of setae on scape and pedicel, shape of distal margin of labrum, and length of maxillary palp. New diagnoses and illustrations are provided for R. minantenna and R. trichobasis, as well as a key to the known nymphs of Rivudiva species.